A tale of three fears : why China does not want to be no.1 - Kai, He (2014)
According to the World Bank, Chinese GDP in Purchasing Power Parity (PPP) terms will surpass the US’, becoming No. 1 in the world, late this year. The Chinese government seems uneasy with this breaking news. Why? What does this mean for its maritime disputes?